Analysis of Factors Affecting Growth of Pension Mutual Funds in Turkey - AçıkgÃ¶z, Ersin; Uygurtürk, Hasan; Korkmaz, Turhan (International Journal of Economics and Financial Issues, 2015)
In this study, the level of relationship between the real growth rate of the stock pension mutual funds that have been involved in the individual pension system and the variables such as the number of fund participants, the real fund returns, fund operating expenses and share of fund assets to the total assets of the funds are analyzed with panel data methodology. The results have reported that apart from the fund operating expenses, the selected independent variables are statistically significant on the the real growth rate of the stock pension mutual funds. Keywords: private pension funds; panel data; growth; Turkey. JEL Classifications: C33; G22; G23